Avaliação da informação de websites turísticos das cidades-sede da copa 2014 - Cacho, Andréa do Nascimento Barbosa (2011)
This study aims to analyze tourist information provided by the official websites of the 2014 FIFA World Cup host cities. The framework developed by Díaz (2005) was applied to analyze different aspects, such as: local tourist information, tourist services distribution, communication and interaction between website and users, and website foreign language versions. This dissertation describes how society and tourism are related by analyzing the consequences of technological evolution in the travel and tourism sector, showing the importance of the use of information and communication technology to provide accurate, upto- date and low-cost information to tourist destinations. Because of the nature of the study, the research subjects are the 12 Brazilian host cities represented by their respective official webpages (cities, states and convention bureaus), and also Brazil s official website, totalizing 36 elements to be analyzed. The methodology has been characterized as descriptive and exploratory with quantitative analysis, and also using desk research and survey literature review. In order to analyze the data collected, parametric and nonparametric statistics tests were used, such as: variance analysis (ANOVA and KRUSKAL-WALLIS) to measure means variance between groups combined with multiple comparison tests (Tukey and Games Howell); nonparametric correlations tests (Kendall s Tau b); and cluster analyses. Finally, Microsoft Excel was used to collect data and SPSS for managing data through quantitative analyses tests. Overall, the websites of the south region showed better results than the other Brazilian regions. Despite this result, the data analysis demonstrated that the available tourist information are incomplete as it was verified that tourist host cities websites are unable to provide all the information needed for the web visitors to organize and plan their journey. This means that visitors have to look for more information in other sources